The Effect of Combining Organic Material and SP – 36 Fertilizer on Phosphorus Availability and Growth of Maize on Ultisol - muhammad syaid rangkuti; fauzi jamal; hamidah hanum (Universitas Sumatera Utara, 2018)
This research aimed to know the effect of combining organic material and SP – 36 fertilizer on phosphorus availability and growth of maize on Ultisol. The research was conducted in the screen house and chemical and soil fertility laboratory, Faculty of Agriculture, University of Sumatera Utara on January – April 2017. This rearch used randomized block designed which consist of 2 factor and 3 replication. The first factor combining organic material which consist of 6 combining : B0 (control), B1 (100% Tithonia diversifolia compost), B2 (75% Tithonia diversifolia compost + 25% chicken manure), B3 (50% Tithonia diversifolia compost + 50% chicken manure), B4 (25% Tithonia diversifolia compost + 75% chicken manure), (100% chicken manure). The second factor of SP – 36 fertility which consist of 4 level : P0 (control), P1 (50 kg/ha P2O5), P2 (100 kg/ha P2O5), P3 (150 kg/ha P2O5). The result showed that the combining of organic material significantly increased soil pH, soil C – Organic, soil P-available, plant height, dry weight of hoot and dry weight of root plant. The application of SP – 36 fertilizer significantly increased soil pH, soil P –available, dry weight leaf and dry root plant. The interaction of combining organic material and SP – 36 fertilizer significantly increased soil P-available, dry weight of hoot and dry root plant. The best interaction 50% Tithonia diversifolia compost + 50% chicken manure and 150 kg P2O5/ha significantly increased soil P-available, dry weight of hoot and dry root plant.